Analysis of New Students' Science Process Skills Readiness and Its Impact on Basic Physics Learning Outcomes 1 - Afriyani; Juniar Afrida; Zahriah (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
Mastery of science process skills (SPS) is a key foundation in physics education at the university level for building conceptual understanding and scientific thinking skills. Although crucial, first-year students generally have very heterogeneous practical skills due to their diverse educational backgrounds. This study aims to investigate the correlation between SPS and the learning outcomes of the 2024 cohort of students in the Basic Physics 1 course in the Physics Education Study Program at UIN Ar-Raniry Banda Aceh. This study used a quantitative correlational design with purposive sampling techniques on 20 students. Data were collected through the SPS test instrument and documentation of final course grades. Data analysis was performed using Spearman's Rho correlation test, considering that the data were not normally distributed based on the Shapiro Wilk test results. The results showed a significant relationship between KPS and learning outcomes with a correlation coefficient of 0.431 (ρ=0.029) which is classified as moderately strong. An interesting finding in this study highlights the very high gap in SPS mastery among new students, which is inversely proportional to their relatively homogeneous academic achievements. This phenomenon indicates an imbalance between psychomotor competencies in practical work and students' cognitive achievements. Based on these findings, standardizing and strengthening practice-based learning at the beginning of the lecture period is a strategic step needed to minimize the gap in student abilities and improve the quality of physics education comprehensively.